Gambaran Kejujuran sebagai Landasan Keutamaan Moral Mahasiswa yang sudah Pernah Mengambil Mata Kuliah Character Building - Wulandari, Antonina Pantja Juni (Humaniora, 2012)
This research sees an overview of honesty as the basis of students’ moral virtue who had taken courses Character Building at Bina Nusantara University. An honest person is one who has the power of the heart goes to the rules and principles of righteous living. Gea, Wulandari, & Babari (2002) conclude that if people have the virtue of honesty, they will not lie or cheat, even though they had the opportunity to do so. Moral virtue is a permanent and stable trend. Virtue is a good trait ingrained in one. The virtue relates to the will, as it relates to the will of the intent or motivation of the performer to be very important, so it is definitely virtuous behaviors with good intentions. The virtue is gained through the process of getting used to and practices. Virtue makes people be good personally (Bertens, 2002). By doing honest means the individual is said to have a moral virtue. The results were distributed to students who got the courses. From the results of the data on the questionnaire distributed to the students who got CB courses as 161 people, results of their honesty are not low. Most of the honesty they got was 61.7%, while the highest honesty is 38.3%.